Routine Preoperative Coagulation Tests in Children Undergoing Elective Surgery or Invasive Procedures: Are They Still Necessary?. Issue 12 (January 2019) - Alzahrani, Azzah; Othman, Nada; Bin-Ali, Tahani; Elfaraidi, Huda; Al Mussaed, Eman; Alabbas, Fahad; Sedick, Qanita; Albatniji, Fatma; Alshahrani, Ziyad; Asiri, Mohammed; Alsuhaibani, Omar; Elyamany, Ghaleb
Introduction: Preoperative coagulation screening tests in pediatric patients was once routine clinical practice globally and still used as standard practice in some countries before surgical procedures to assess of perioperative bleeding risk. Objective: The study aimed to evaluate unselected routine preoperative coagulation testing in children undergoing elective or invasive surgery to predict abnormal perioperative bleeding. The study also aimed to provide a rational approach of determining bleeding and family history of coagulation disorders as a predictive risk for bleeding. Methods: This retrospective study conducted between 2014 and 2015 (1 year) on normal healthy children aged under 15 years admitted to the hospitals for elective mild to intermediate surgery or invasive procedures. We reviewed and collected the details of the clinical history, previous surgery, trauma, family history, detail of anti-thrombotic medication and coagulation tests performed (prothrombin time (PT), the activated partial prothrombin time (APTT), and international normalized ratio (INR)) at the time of admission. Results: Among 2078 cases, 1940 cases had normal coagulation tests (93.4%), 77 cases had abnormal coagulation results (3.7%), and 61 patients underwent surgery without preoperative coagulation screening (2.9%). In 15 of 77 patients, coagulation tests were normal on repeat testing. A total of 52 were confirmed to have abnormal screening testing. Among these 52 cases, 45 had normal factors assay; where seven patients had abnormal factors assay. Postoperative bleeding occurred only in three cases (0.14%), two cases due to surgical procedures with normal preoperative testing and one due to hemophilia A which was detected postoperatively as no preoperative testing was performed. Conclusions: Routine coagulation screening before surgery or invasive procedures to predict perioperative bleeding in unselected patients is not recommended. Our study emphasizes that selective preoperative testing is more appropriate. Selective criteria for consideration of the latter includes physical examination, type of surgery, family and bleeding history, and concomitant use of antiplatelet and anti-thrombotic therapy.